Synthesis and analysis of 4-(3-fluoropropyl)-glutamic acid stereoisomers to determine the stereochemical purity of (4S)-4-(3-[18F]fluoropropyl)-L-glutamic acid ([18F]FSPG) for clinical use - Shih, Kai-Ting; Huang, Ya-Yao; Yang, Chia-Ying; Cheng, Mei-Fang; Tien, Yu-Wen; Shiue, Chyng-Yann; Yen, Rouh-Fang; Hsin, Ling-Wei (PloS one, 2020)
(4 S )-4-(3-[ 18 F]Fluoropropyl)-L-glutamic acid ([ 18 F]FSPG) is a positron emission tomography (PET) imaging agent for measuring the system x C − transporter activity. It has been used for the detection of various cancers and metastasis in clinical trials. [ 18 F]FSPG is also a promising diagnostic tool for evaluation of multiple sclerosis, drug resistance in chemotherapy, inflammatory brain diseases, and infectious lesions. Due to the very short half-life (110 min) of 18 F nuclide, [ 18 F]FSPG needs to be produced on a daily basis; therefore, fast and efficient synthesis and analytical methods for quality control must be established to assure the quality and safety of [ 18 F]FSPG for clinical use. To manufacture cGMP-compliant [ 18 F]FSPG, all four nonradioactive stereoisomers of FSPG were prepared as reference standards for analysis. (2 S ,4 S )- 1 and (2 R ,4 R )- 1 were synthesized starting from protected L- and D-glutamate derivatives in three steps, whereas (2 S ,4 R )- 1 and (2 R ,4 S )- 1 were prepared in three steps from protected ( S )- and ( R )-pyroglutamates. A chiral HPLC method for simultaneous determination of four FSPG stereoisomers was developed by using a 3-cm Chirex 3126 column and a MeCN/CuSO 4(aq) mobile phase. In this method, (2 R ,4 S )- 1 , (2 S ,4 S )- 1 , (2 R ,4 R )- 1 , and (2 S ,4 R )- 1 were eluted in sequence with sufficient resolution in less than 25 min without derivatization. Scale-up synthesis of intermediates for the production of [ 18 F]FSPG in high optical purity was achieved via stereo-selective synthesis or resolution by recrystallization. The enantiomeric excess of intermediates was determined by HPLC using a Chiralcel OD column and monitored at 220 nm. The nonradioactive precursor with >98% ee can be readily distributed to other facilities for the production of [ 18 F]FSPG. Based on the above accomplishments, cGMP-compliant [ 18 F]FSPG met the acceptance criteria in specifications and was successfully manufactured for human use. It has been routinely prepared and used in several pancreatic ductal adenocarcinoma metastasis-related clinical trials.